IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH THREE MINUTE PAUSE STRATEGY - Radiah Hamid; Musriana Musriana; Bahrun Amin; Nur Qalby (Universitas Muhammadiyah Makassar, 2017)
This research aimed to explain the improved of the students’ reading comprehension in terms of literal comprehension dealing with main idea and details and summarizing dealing with content and logical order. A classroom action research which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken at X students of SMA Gunung Sari Makassar with a number of the subject were 20 students. The research findings indicate that the application of Three Minute Pause strategy was significant in improving the students’ reading comprehension in terms of literal comprehension and summarizing. It was proved by the mean score of the cycle I was 6.88then increased to be 7.87 in cycle II. They were higher than the mean score of diagnostic test namely 4.77. It means that there was the improved of the students’ reading comprehension in terms of literal comprehension dealing with main idea and details and summarizing dealing with content and logical order.Keywords: literal comprehension; action research; strategy; content; logical order